2017
DOI: 10.3390/su9061016
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Company-Cause Fit and Company Involvement in Consumer Responses to CSR Initiatives: A Meta-Analytic Review

Abstract: Abstract:The marketing literature suggests that company-cause fit is of key importance to developing a successful socially responsible initiative. However, controversy exists regarding the level of this fit. While some studies report that high fit between a company and a cause has beneficial effects on consumer responses to such efforts, other research identifies negative impacts. This paper aims to obtain a deeper insight into this issue by examining the moderating role of company involvement in a cause. A me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 84 publications
1
24
0
3
Order By: Relevance
“…Likewise, Alshammari [44] contended that CSR contributes to building a better image with stakeholders. Zasuwa [23] also found that CSR activities reinforce consumers' beliefs that the firm is reliable and trustworthy, thereby contributing to building a better corporate reputation. By focusing on the hotel industry, Kim and Kim [24] corroborated that the involvement in CSR contributes to a better reputation through customer satisfaction and trust [45,46].…”
Section: Csr Performance and Foreign Ownershipmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, Alshammari [44] contended that CSR contributes to building a better image with stakeholders. Zasuwa [23] also found that CSR activities reinforce consumers' beliefs that the firm is reliable and trustworthy, thereby contributing to building a better corporate reputation. By focusing on the hotel industry, Kim and Kim [24] corroborated that the involvement in CSR contributes to a better reputation through customer satisfaction and trust [45,46].…”
Section: Csr Performance and Foreign Ownershipmentioning
confidence: 99%
“…This indicates that from the host firm's perspective, foreign investment can be incentivized by managing inter-relationships with their stakeholders, or how they are evaluated by their stakeholders [18][19][20][21][22][23][24][25]37]. From this standpoint, we argue that foreign investors, who want to avoid uncertainty and information asymmetry in investing in firms in different countries, are likely to have favorable attitudes for the host firms that actively engage in CSR activities.…”
Section: Csr Performance and Foreign Ownershipmentioning
confidence: 99%
See 2 more Smart Citations
“…Through CSR investment, enterprises can attract responsible consumers, obtain financial resources from investors with strong social responsibility, facilitate financing, or help struggling companies to recover from financial distress [8][9][10][11]. Scholars have found that CSR is positively related to financial performance and that CSR can improve stakeholder interests, ultimately leading to better financial performance [12][13][14]. On the contrary, failure to meet the expectations of stakeholders creates fear in the market and ultimately a loss in profitability [15].…”
Section: Literature Reviewmentioning
confidence: 99%